Group word terms in the terminology of the theory of mechanics in Albanian and English - PLLANA, GANI; PLLANA, SADETE (Journal of Education Culture and Society, 2020)
As it is known, the terminology of any knowledge field as an independent system, as well as the terminology of mechanics consisting of nominating one-word and group word units (among which, particularly the latter phrase terms) make up nearly 70-80% of the overall terminological vocabulary. Looking at it from this point of view, all mono-syllabic (one word) terms (word terms) would also be accepted as a basic vocabulary in the terminology of mechanics. This can be justified more so by the fact that almost every word term serves as the foundation for the construction of numerous group word terms that mark concepts which have spread out into numerous branches. These having been introduced through a variety of many different interrelations, like gender / type, whole / part etc.